A novel algorithm : apriori-ant. The combination of apriori algorithm and ants colony optimization algorithm - Choo, Ai Ling (Faculty of Computer Science and Information Technology, 2005)
This thesis explores an innovative technique to extract data from a vast number of patients' records and then generate them into useful rules that can be used in an Expert System. Material used for the study of this thesis is a set of Skin Burn data.